PEMILIHAN BIBIT KELINCI NEW ZEALAND WHITE (NZW) TERBAIK DENGAN MENGGUNAKAN METODE VIKOR - Mulyati Mulyati; Erniyati Erniyati (Ilmu Komputer, FMIPA, Universitas Pakuan, 2021)
The New Zealand White (NZW) rabbit is a rabbit originating from America that has now spread to Indonesia. NZW rabbits have the advantage that they have large meat weight, small bones and a harvest period of about 3.5 months. However, the quality of the rabbits produced is very influential in the initial selection of seeds. Therefore, a decision support system is needed to select so that the resulting rabbits are as expected. One of the selection methods used in selecting the best rabbit seeds is the Visekriterijumsko Kompromisno Rangiranje (VIKOR) method. VIKOR is a decision-making method that works by looking at the closest solution / alternative as an approach to the ideal solution in ranking. The purpose of this study is to recommend the selection of the best NZW rabbit seeds using the VIKOR method. The results showed that the VIKOR method was able to select the best NZW Rabbit seeds from a number of existing data.